2019
DOI: 10.1108/jmtm-08-2019-0291
|View full text |Cite
|
Sign up to set email alerts
|

Investigating broker centrality in innovation-driven networks

Abstract: Purpose In contrast to the vertical supply chain structure, firms are increasingly engaging in horizontal inter-firm collaborations to develop new technologies, products and services, yet, little is known about factors that influence the governance mechanism and performance of such collaborative projects. The purpose of this paper is to investigate how different factors affect the role or the centrality of the governing mechanism (the broker) in inter-firm collaborative networks. Design/methodology/approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…(3) The role of a broker as a network manager (Macchi et al, 2014;Idiagbon-Oke & Oke, 2019;Leick & Gretzinger, 2020;Srivastava, 2020). In networks composed of various actors, the task of brokers is to facilitate the flow of knowledge and information (Pyka & Janiszewski, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) The role of a broker as a network manager (Macchi et al, 2014;Idiagbon-Oke & Oke, 2019;Leick & Gretzinger, 2020;Srivastava, 2020). In networks composed of various actors, the task of brokers is to facilitate the flow of knowledge and information (Pyka & Janiszewski, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These network advantages can increase the innovativeness of enterprises and stimulate innovation processes" (Leick & Gretzinger, 2020, p. 840). As part of the network, companies combine complementary resources, share information and collaborate to achieve common goals (Idiagbon-Oke & Oke, 2019). The sum of knowledge acquired by companies is a key resource for achieving a competitive advantage (Crupi et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent work has shown that centrality in a supply chain network can be a key determinant of innovation (Gnekpe and Coeurderoy, 2017; Idiagbon-Oke and Oke, 2020; Sun and Gong, 2020). In other words, some firms have greater innovation potential.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few notable studies that have investigated the benefits a firm derives from its central position in a network (e.g. Idiagbon-Oke and Oke, 2020; Sun and Gong, 2020; Rachinger et al , 2019). Most previous studies have centered on how firms can manage network coordination mechanisms, manufacturing modularity or business networks (Chandrashekar et al , 2018; Cheng et al , 2021; Deflorin et al , 2021; Shen et al , 2019; Slepniov et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation